Performance and Emission study of supercharged IDI diesel engine using Beef Tallow Methyl Ester with ethanol as an additive - P Santosh Babji, Ganapathi Vedulla Aditya kolakoti, B V Appa Rao (International Journal of Scientific Research and Management (IJSRM), 2017)
Beef Tallow Methyl Ester (BTME) was tried in an Indirect Diesel Injection (IDI) engine with super charger and secondary injection of hydrated ethyl alcohol as an additive at the suction end. The additive was injected at 3bar in to the incoming air without affecting the breathing capacity of the engine. Alcohol injection is resorted to ensure low temperature combustion. The additive starting from 2% to 8% was injected in steps of 2% increase. For all these percentages of additive, the combustion pressures and tail pipe emissions were measured to compare the engine performance in these aspects with respect to diesel fuel. The experimentation revealed that the biodiesel with 2% hydrated ethyl alcohol proved to be befitting replacement to the diesel fuel.